Improving Mechanism for Selection and Execution of Projects under Non-Lapsable Central Pool of Resources and North East Council - Planning Commission (Planning Commission, Government of India, 2006)
The document on Mechanism Improvement for Project Management under NLCPR & NEC Funds addresses challenges in the planning, sanctioning, and execution of development projects funded by the Non-Lapsable Central Pool of Resources (NLCPR) and the North East Council (NEC) in India’s Northeastern States (NER). Despite significant financial allocations, project outcomes have often been ineffective due to deficiencies in project selection, delays in approvals, and insufficient local capacity for preparation and management of Detailed Project Reports (DPRs). Chief Ministers and stakeholders highlighted the need for equitable project prioritization, clarity in fund allocation, and streamlined administrative processes, while DoNER’s coordination mechanisms remain underutilized. The report recommends strengthening regional planning capacity, establishing a “shelf of projects” based on regional and sectoral needs, implementing equitable fund distribution formulas, outsourcing DPR preparation when required, and enabling autonomous appraisal by sponsoring agencies. It also emphasizes unified sanctioning frameworks, real-time online monitoring, independent evaluation of major projects, and proper transference of assets for sustainable operation. Additionally, the creation of an Infrastructure Development Fund (IDF) is proposed to consolidate resources, enhance accountability, and reduce redundancies in infrastructure funding. Collectively, these measures aim to bridge the gap between financial inputs and tangible development outcomes, ensuring that central investments in NER translate into effective infrastructure and socioeconomic improvements.
Planning Commission Government of India August, 2006
Keywords: NLCPR Funds; NEC Funds; Project Management; Northeastern States; Detailed Project Reports; Regional Planning; Fund Allocation; Monitoring and Evaluation; Infrastructure Development; DoNER; Project Sanctioning; Accountability